Cryolipolysis and Skin Tightening - Carruthers, Jean; Stevens, W. Grant; Carruthers, Alastair; Humphrey, Shannon (Dermatologic surgery, 2014)
BACKGROUNDAnecdotally, there have been reports of skin tightening after cryolipolysis, but this has not been studied or reported in the literature. OBJECTIVEThis clinical evaluation of patients treated with cryolipolysis in the thighs, abdomen, arms, and back assesses changes to skin texture, laxity, and cellulite at 2 study centers. METHODSFrom the Vancouver site, a comprehensive review of cryolipolysis treatments was performed to assess treatment areas and retreatments. While reviewing data, investigators were struck by the noticeable skin tightening shown in clinical photographs. Subsequently, a survey of Vancouver patients was conducted to assess changes to skin texture and laxity. At the Marina del Rey site, subjects undergoing a clinical study for lateral thigh cryolipolysis were evaluated for changes to skin texture, laxity, and cellulite. RESULTSIndependent assessments by patients and investigators found consistent improvement in skin texture and laxity for treatments to the outer thighs, abdomen, arms, and back. Outer thighs also showed mild-to-moderate improvement in cellulite. CONCLUSIONThis clinical evaluation demonstrates consistent improvement in skin texture, laxity, and cellulite after cryolipolysis as independently assessed by patients and investigators. Prospective clinical studies should be conducted to objectively study and quantify skin tightening after cryolipolysis.